The Development of Islamic Financial Instrument: Opportunities and Challenges - Samudera, Ahmad Bayu; Ismail, Depid; Suhendi, Suhendi; Muslim, Sarip (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
Islamic financial instruments are an integral component of the global economic system, particularly in countries with a majority Muslim population. The growing Muslim population and increased awareness of Islamic compliance are driving the use of Islamic financial instruments as an alternative to conventional options. This study aims to explore the development, challenges, and opportunities of Islamic financial instruments using a descriptive qualitative research approach. Data collection techniques involve literature review with secondary data sourced from academic journals, official publications, and reports on Islamic financial developments from various institutions. The results of this study indicate that there are various Islamic financial instruments, such as murabahah and mudharabah, used for Islamic funding instruments, as well as other instruments for Islamic financing instruments, Islamic savings and deposit instruments, Islamic investment instruments, Islamic insurance instruments, and social Islamic finance instruments. There is also the development of Islamic financial instruments like green sukuk and Islamic financial technology. However, this development faces challenges, including regulatory and policy issues, liquidity challenges, and others. It is hoped that this research will contribute to the expansion of Islamic financial instruments and raise awareness among the public, particularly among academics and practitioners, to address the challenges in Islamic finance.